Design of Web-Based Material Management Information System in Financial Module (Case Study PT INTI) - Selvyananda Adelita Vanesia; Rachmadita Andreswari; Faishal Mufied Al Anshary (International Journal of Innovation in Enterprise System, 2018)
PT INTI engaged in telecommunication, has long become a supplier of network construction with a large scale that is national. Therefore, PT INTI has a lot of material and spread all over the city in Indonesia. Previously, PT Inti still uses semi-manual way to do their material recording. The material recording is done by using Microsoft Excel which will be sent by electronic mail (email) if needed. But it is vulnerable to errors because the data contained in is not integrated. To overcome this, PT INTI wants to have a web based application called INTI Maintenance to manage financial materials such as material input, material search, material removal, material search, material data printing, to finance such as request addition, change of request status, delivery, and residual balances of each city. INTI Maintenance web-based information system financial module is built with open source software that uses PHP as the programming language, MySQL as the database, and Windows as server computer. The final results achieved in the material management information system in this module have advantages in assisting PT INTI employees in managing financial data and validation for material delivery using receipt of delivery material. Keywords—information system, management, material, finance.